Analisis keberhasilan dan kegagalan dalam antisipasi penjaga gawang futsal putra pada Kejuaraan Brandon Ramadhan Cup 2022 - Setyojati, Damar Mulyo; Ridlo, Azi Faiz (Motion: Journal Research of Physical Education, 2022)
The purpose of this study is to describe what is happening at the time of the match. The researcher uses this research design because the researcher wants to know and give an overview of what is in the match. In this study, researchers made direct observations by calculating the number of anticipations made by male futsal goalkeepers in the form of percentages in each match. The situation of anticipation of goalkeepers in several matches analyzed, there are many anticipations that can be done by futsal goalkeepers. The total percentage of the success rate of anticipation of futsal goalkeepers is 100% with a total of 60 times anticipating successful and the total percentage of failure rates of anticipating futsal goalkeepers is 46.7% with a total of 42 times anticipating failure.